2003
DOI: 10.1111/1467-7687.00271
|View full text |Cite
|
Sign up to set email alerts
|

Two‐month‐old infants match phonetic information in lips and voice

Abstract: Infants aged 4.5 months are able to match phonetic information in the face and voice (Kuhl & Meltzoff, 1982;Patterson & Werker, 1999); however, the ontogeny of this remarkable ability is not understood. In the present study, we address this question by testing substantially younger infants at 2 months of age. Like the 4.5-month-olds in past studies, the 2-month-old infants tested in the current study showed evidence of matching vowel information in face and voice. The effect was observed in overall looking tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
234
2
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(245 citation statements)
references
References 27 publications
8
234
2
1
Order By: Relevance
“…As a result, we predicted that young infants would match monkey faces and voices, but that older infants would not. This finding would differ markedly from previous findings showing that infants can match human faces and voices as early as 2 months of age and as late as 12 months of age (1)(2)(3)(4)(5)(6)(7)(8).…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…As a result, we predicted that young infants would match monkey faces and voices, but that older infants would not. This finding would differ markedly from previous findings showing that infants can match human faces and voices as early as 2 months of age and as late as 12 months of age (1)(2)(3)(4)(5)(6)(7)(8).…”
contrasting
confidence: 99%
“…However, given the nature of the methodology, this was impractical: infants typically do not tolerate more than the four test trials in a testing session. Also, a large body of evidence shows clearly that human infants as young as 2 months of age and as old as 12 months of age can make intraspecies (human face-voice) intersensory matches in the same kind of task used here (1)(2)(3)(4)(5)(6)(7)(8). Thus, it is unlikely that the subjects used in the current study would be exceptional in this capacity.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…This is a combination response rather than a fusion response [Omata & Mogi, 2008].) Although there is no evidence that infants are capable of integrating auditory and visual speech information into a single percept before 4.5 months of age (see above), Patterson and Werker (2003) showed that infants as young as 2 months are sensitive to (co-occurring) matching/mismatching audio-visual speech stimuli.…”
Section: The Current Taskmentioning
confidence: 99%
“…Infants with normal hearing demonstrate sensitivity to auditory-visual integration processes within the first few months of life (Burnham & Dodd, 2004;Lewkowicz, 2000;Patterson & Werker, 2003). Children with hearing loss who had received a cochlear implant after 30 months of age did not consistently report fused auditory-visual percepts in a McGurk stimuli task (Schorr, Fox, van Wassenhove, & Knudsen, 2005).…”
Section: Considerations For the Erp Resultsmentioning
confidence: 99%